Systemic effects of fluticasone on blood eosinophils in bronchiectasis. Issue 3 (3rd September 2020) - Lipworth, Brian; Chan, Rory; Kuo, Chris RuiWen
We read with interest the observations of Aliberti et al. [1] showing that blood eosinophilia predicts the quality of life response to inhaled fluticasone propionate (FP) in bronchiectasis, apparently independently of concomitant asthma or COPD. Pointedly they only appeared to have measured blood eosinophils at baseline and not during treatment with FP. This is pertinent as FP produces dose-dependent suppression of blood eosinophils due to systemic absorption from the lung. Hence, 1 mg of inhaled fluticasone in asthma patients is systemically equivalent to 5.3 mg of oral prednisolone for blood eosinophil suppression and 8.5 mg for cortisol suppression [2]. We would therefore be interested to know if similar improvements in quality of life occur in bronchiectasis in relation to blood eosinophilia with other inhaled corticosteroids (ICS) that exhibit much less systemic glucocorticoid potency, such as budesonide or beclmomethasone [3]. Also, it would be interesting to know if patients with bronchiectasis who have other elevated type-2 biomarkers, such as fractional exhaled nitric oxide, might also benefit from either inhaled FP or other ICS [4]. Fluticasone response in bronchiectasis may be explained by its systemic eosinophil suppression https://bit.ly/3dDd74E